2018
DOI: 10.24924/ijise/2018.11/v6.iss2/93.115
|View full text |Cite
|
Sign up to set email alerts
|

Gamifying a Flipped First Year Accounting Classroom Using Kahoot!

Abstract: Accounting is often perceived as boring, difficult, methodical and being all about number crunching by a lot of students and society in general. These negative perceptions impact on students' learning and their approach to the study of accounting. Additionally, studying accounting in English as a second language as well as in the first year of university compounds the amount of problems students may face, adversely affecting their performance. In a bid to address these problems, the flipped classroom approach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 113 publications
(72 reference statements)
0
6
0
1
Order By: Relevance
“…Susanti (2017) found that Kahoot helps students express their point of view in class and wakes them up from their slumber in class. In the same vain, Nkhoma, Nkhoma, Thomas and Tu (2018) reported that Kahoot provides feedback, helps check students' understanding and give the lecturer the opportunity to engage with a large number of students. Furthermore, ISSN 1927-6028 E-ISSN 1927 Kahoot is also reported to increase class participation (Parra-Santos, Molina-Jorda, Casanova-Pastor & Maiorano-Lauria, 2018) and reduce teacher's workload (de Sousa, 2018).…”
Section: Teachers' Perceptions Of Kahootmentioning
confidence: 99%
“…Susanti (2017) found that Kahoot helps students express their point of view in class and wakes them up from their slumber in class. In the same vain, Nkhoma, Nkhoma, Thomas and Tu (2018) reported that Kahoot provides feedback, helps check students' understanding and give the lecturer the opportunity to engage with a large number of students. Furthermore, ISSN 1927-6028 E-ISSN 1927 Kahoot is also reported to increase class participation (Parra-Santos, Molina-Jorda, Casanova-Pastor & Maiorano-Lauria, 2018) and reduce teacher's workload (de Sousa, 2018).…”
Section: Teachers' Perceptions Of Kahootmentioning
confidence: 99%
“…It is postulated that this is achieved by Kahoot's propensity to influence classrooms dynamics through the development of a competitive, interactive and collaborative classroom that motivates engagement with lecture content thereby fostering deep learning practices (Bicen & Kocakoyun, 2018;Licorish et al, 2018). Indeed, Kahoot has been credited with enabling students to speak out in class, providing a means to seek feedback immediately upon performance, and more recently attributed with permitting engagement of large numbers of students at the same time (Nkhoma, Nkhoma, Thomas, & Tu, 2018;Parra-Santos, Molina-Jorda, Casanova-Pastor, & Maiorano-Lauria, 2018;Wang & Tahir, 2020). These are indeed important attributes, as many researchers advocate that student engagement and motivation are key to eliciting meaningful learning (Biggs & Tang, 2011;Meguid & Kahalil, 2017).…”
Section: Kahootmentioning
confidence: 99%
“…In another study, gamification in the evaluation process reduced exam anxiety (Isbister et al, 2012). Also, Nkhoma, Nkhoma, Thomas, Tu, and Le (2018) claimed that Kahoot! removed stress and brought fun to the class.…”
mentioning
confidence: 99%